Parâmetros relacionados à depressão em animais adultos submetidos à ativação imune neonatal - Marzzani, Simone Helena Schelder (2018)
Introduction: The pathophysiology of depressive disorders still remains misunderstood. Despite the all the contributions of the monoaminergic hypothesis, several studies have evidenced the role of neuroinflammation into the development of depression. A neuroinflammation can modulate permanent or encephalic development, the immune and endocrine regulation as well as neural circuits, which canresul in physiological and behavioral changes. Objective: To verify an association between a neonatal immune activation and parameters related to depression in the adult life using an animal as model. Methods: C57BL/6 animals with two days old were exposed to LPS or PBS. When the animals completed 46 days old, it received PBS or Imipramine for 14 days. At the end of 60th day of their lives, it were evaluated the consumption of sucrose; the time of immobility; the weight of the adrenal gland and the hippocampus; levels of plasma corticosterone and hippocampal BDNF. Results: It shows that the animals exposed to LPS in the neonatal period and evaluated in adult life showed a decrease in the consumption of sucrose; an increase in immobility time; reduction of hippocampus weight; an increase in the weight of the adrenal gland and an increase in plasma levels of corticosteroids. The use of imipramine only did not reverse the decrease hippocampal weight. Regarding hippocampal BDNF levels, there were no changes. In conclusion, these results suggest that neonatal immune activation may be associated with depression-like parameters in adult life. It is believed that endotoxemia can trigger physiological and behavioral, increasing vulnerability to the development of depression in adult life.